Determinants of capital structures based on the Pecking Order Theory and Trade-off Theory - Hotman Jefferson Simatupang; Lilik Purwanti; Endang Mardiati (Jurnal Keuangan dan Perbankan, 2019)
Determining the decision of the company's capital structure is a very important thing because it influences the development of resources potency and the sustainability of a company. Related to deciding on the capital structure, there is still a different perception so far between pecking order theory and trade-off theory. This research aims to know the effect of profitability, sales growth, non-debt tax shield, the tangibility of assets, and funding surplus towards the capital structure of non-financial companies listed in Indonesia Stock Exchange (IDX) period 2014-2017. The research method used was Causal-Comparative Research with samples investigated were panel data of 154 non-financial companies experiencing funding surplus with total observation in the amount of 616. The result of this research shows that non-debt tax shield and growth sales do not affect the company's capital structure. Besides that, funding surplus has a positive effect on the capital structure, while profitability and tangibility assets have a negative effect on the capital structure.JEL Classification: C33, G02, G32DOI: https://doi.org/10.26905/jkdp.v23i1.2579